Lessons from Small-Scale Fish Farming in South West and West Shewa Zone, Oromia Region, Ethiopia. A Review - Mesfin, Yared; Yami, Mesay; Tesfaye, Gashaw (Journal of Agriculture and Environmental Sciences, 2021)
For the past 13 years, the National Fisheries and Aquatic Life Research Center (NFALRC) haveintervened with small-scale fish farming trials in South West and West Shewa zones of Oromia Region, Ethiopia.Opportunities and challenges of the trial, farmers’ awareness, and attitude towards small-scale fish farming and itseconomics have already been studied and documented. However, the studies were not comprehensively reviewed,synthesized, and presented to inform further intervention. This paper is meant to fill this gap. Desk review of thosestudies and others supported by prior experience of the author to intervention areas is the core approach followed.As a result, seven key lessons were learned: the need for redefining core challenges of small-scale fish farming,gender inclusion in small-scale fish farming, need for a revision of public sector-led formal extension servicedelivery linked to the change in the conventional extension approach followed by NFALRC, emphasis on awarenesscreation on fish farming, the importance of participatory approaches and the need for repeating research trials inthe economics of small-scale fish farming. Among these, awareness creation, the use of participatory approaches,and changes in conventional extension service delivery by NFALRC should be given priority.